З історії археологічного вивчення території Житомирщини в рамках підготовки «Зводу пам'яток історії та культури народів СРСР» 1985—1990 рр. - Вітрик, І.С. (Археологія і давня історія України, 2017)
У статті висвітлюється історія та досвід
роботи над темою «Археологічні пам'ятки Житомирської області» в рамках підготовки «Зводу
пам'яток історії та культури народів СРСР», здійсненої групою по вивченню Змійових валів Інституту археології АН УРСР під керівництвом М. П. Кучери протягом 1984—1991 рр. В статье освещена работа над темой «Свод памятников истории и культуры народов СССР. Раздел:
Археологические памятники Украинской ССР. Подразделение Археологические памятники Житомирской области» группы по изучению Змиевых валов
Института археологии АН УССР под руководством М. П. Кучеры в течение 1984—1991 гг. The article highlights the hard work on theme of
«The Code of historic and cultural memorials of the
USSRs people. Category: Ukrainian SSR archaeological
sites. Subcategory: Zhytomyr oblast archaeological
sites» by the group, which was exploring Serpents Wall
(defensive system of X—XI centuries) under the direction
of M. Kuchera in 1984—1991s. During this period
the materials about almost 500 locations from the late
Paleolithic to the Late Middle Ages in Zhytomyr oblast
were collected on archival and literature sources. Simultaneously
archaeological surveys of nearly 100 known and new monuments were conducted. This information
should be a part of the book «Zhytomyr oblast archaeological sites», but it still has not been published.